Relationship between fish community and riparian vegetation cover in hydrological periods (Coffee-growing region, Colombia). - Pérez-Mayorga, María Angélica; Laboratorio de Ictiología 108b, Edificio 53, Pontificia Universidad Javeriana, Carrera 7ª. No. 40-62, Bogotá D.C., Colombia (Pontificia Universidad Javeriana, 2011)
Objective. To assess the relationship between structure and diet of the fish community and the riparian vegetation cover (RVC), in two hydrological periods (HYPE) in streams of the La Vieja river basin. Materials and methods. Collections were done with electrofishing and rapiché in March and May 2010. Efficiency of sampling effort was assessed with the estimator Chao2. Structure was analyzed using the indices of richness, dominance, diversity and evenness which were compared with an ANOVA. Gastrointestinal contents were analysed with the indices of vacuity coefficient, frequency, volume and food importance. We examined the relationship among diet, HYPE and RVC using the multiple correlation coefficient (r), the coefficient of determination (r2) and a Canonical Correspondence Analysis (CCA). Results. According to the Chao2 estimator, in most streams the fish species richness values are representative. There were no significant differences (P>0.05) among the structural variables, the HYPE and the RVC. According to r and r2 the diet of most fish species did not vary as a function of RVC and HYPE; however, according to the CCA diet varies as a function of HYPE but not of RVC. Conclusions. The fish community structure did not show changes according to RVC and HYPE. Although most species showed no changes in their diet, the community did show changes in diet according to HYPE, due to a change in composition; however diet changes were not detected by RVC. Key words: coffee-growing region, diet, fish community, hydrological period, riparian vegetation cover, structure.